2015
DOI: 10.1089/jir.2014.0155
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble CD14 in Egyptian Patients with Chronic Hepatitis C: Its Relationship to Disease Progression and Response to Treatment

Abstract: Hepatitis C virus (HCV) is a major public health problem. Soluble CD14 (sCD14) level was shown to be associated with HCV infection. In this study, we aimed to investigate the relationship between sCD14 concentration and disease progression, as well as the response to pegylated interferon/ribavirin (peg-IFN/RBV) therapy in Egyptian patients with chronic hepatitis C (CHC). The ELISA technique was used to test 80 patients with CHC and 20 healthy control persons for serum levels of sCD14 (pretreatment and after 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Microbial translocation as determined by elevated sCD14 has been linked with increased mortality among HIV-infected individuals [25] and individuals on haemodialysis [27]. Importantly, sCD14 concentrations are also elevated in hepatitis C virus infection [28], tuberculosis [29], inflammatory disorders such as rheumatoid arthritis and systemic lupus erythematosus [30] and in HIV associated accelerated aging [31]. The diversity of conditions in which sCD14 levels are reported elevated perhaps limits the specificity of the biomarker to any of them thereby limiting its utility as a diagnostic or prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial translocation as determined by elevated sCD14 has been linked with increased mortality among HIV-infected individuals [25] and individuals on haemodialysis [27]. Importantly, sCD14 concentrations are also elevated in hepatitis C virus infection [28], tuberculosis [29], inflammatory disorders such as rheumatoid arthritis and systemic lupus erythematosus [30] and in HIV associated accelerated aging [31]. The diversity of conditions in which sCD14 levels are reported elevated perhaps limits the specificity of the biomarker to any of them thereby limiting its utility as a diagnostic or prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence has suggested that elevated plasmatic levels of soluble CD14 (sCD14) are indicative of bacterial translocation . Recent studies have demonstrated a relationship between sCD14 and hepatic disease outcomes in chronically HCV‐infected individuals . In this study, sCD14 concentrations were not only elevated in plasma from naive and therapy failed CHC patients (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…22 Recent studies have demonstrated a relationship between sCD14 and hepatic disease outcomes in chronically HCV-infected individuals. [23][24][25][26] In this study, sCD14 concentrations were not only elevated in plasma from naive and therapy failed CHC patients (Fig. 5a), but higher levels were detected among those patients with elevated hepatic fibrosis (Fig.…”
Section: Higher Bacterial Translocation Associated With Il-17 Positivmentioning
confidence: 81%
See 1 more Smart Citation
“…Henning et al [28] demonstrate the expansion of CD14+CD16+ monocytes in the circulation and liver of CLD-patients upon disease progression and suggest their functional contribution to the perpetuation of intrahepatic inflammation and profibrogenic HSC activation in liver cirrhosis while Medhat Eman et al 2015 [29] found that The serum sCD14 level was significantly higher in chronic HCV-infected patients compared to healthy control subjects . The serum sCD14 level was significantly directly correlated with the hepatic fibrosis score, histological activity index, and serum aminotransferases.…”
Section: Discussionmentioning
confidence: 99%